O mundo coberto de penas: o vínculo entre ser humano e terra como problema em Vidas secas - Luna Filho, José Roberto de (2021)
Vidas secas is the novel by Graciliano Ramos in which the landscape and the people from Brazilian Northeast most appear. But these people have a relationship with their land that is, at the same time, telluric and hurtful. We analyse that brutal relationship within the chapter O mundo coberto de penas, in order to argue that the condition of the modern subject, which we observe in the book, increases the pain of Fabiano and composes an aesthetic project that refuses dichotomies between universal and particular.